2016
DOI: 10.18632/oncotarget.13301
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib for the treatment of benign and malignant neoplasms from von Hippel-Lindau disease: A single-arm, prospective phase II clinical study from the PREDIR group

Abstract: Von Hippel-Lindau (VHL) disease is an autosomal dominant hereditary cancer syndrome that predisposes affected individuals to the development of multiple benign and malignant tumors. One of the main manifestations of VHL is renal cell carcinoma (RCC). RCC is increasingly being treated with targeted therapies, which offer an alternative treatment option for patients with VHL disease. This study investigated the effectiveness of sunitinib in VHL patients with advanced tumors or tumors unsuitable for surgery.This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…A multicenter, Phase-II, open-label study of sunitinib from the PREDIR VHL network has shown that all five enrolled patients with VHL disease exhibited stable disease as the best response at 6 months. This study also showed that sunitinib was more effective for VHL-related RCCs than for other VHL-related lesions 11 . More recently, a retrospective study by Roma et al showed that 9 of 14 (64%) patients with VHL who received sunitinib treatment as a first-line therapy exhibited radiological response not only in renal and hepatic lesions but also in pancreatic nodules 12 .…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…A multicenter, Phase-II, open-label study of sunitinib from the PREDIR VHL network has shown that all five enrolled patients with VHL disease exhibited stable disease as the best response at 6 months. This study also showed that sunitinib was more effective for VHL-related RCCs than for other VHL-related lesions 11 . More recently, a retrospective study by Roma et al showed that 9 of 14 (64%) patients with VHL who received sunitinib treatment as a first-line therapy exhibited radiological response not only in renal and hepatic lesions but also in pancreatic nodules 12 .…”
Section: Resultssupporting
confidence: 58%
“…In 2009, Jimenez et al reported that a carrier of a VHL germline mutation with an aggressive malignant pheochromocytoma and several RCCs and pancreatic neuroendocrine tumors exhibited decreases in the sizes of most tumors after 6 months of treatment with sunitinib 14 . Furthermore, several other studies 7 , 8 , 11 , 15 have shown that sunitinib may be more effective in cRCCs arising from patients with VHL disease compared to sporadic non-VHL-related RCCs. Previous studies are equivocal, however, with respect to the effects of sunitinib on other VHL-related lesions.…”
Section: Resultsmentioning
confidence: 97%
“…Systemic therapy has been more broadly tested in patients with von Hippel-Lindau disease. Multiple studies reported outcomes in individuals treated with sunitinib(14-16). A 2011 study prospectively evaluated the safety and efficacy of sunitinib in 15 patients with von Hippel-Lindau disease(17).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of tyrosine kinase inhibitors, a single trial and multiple case reports exist in the use of multityrosine kinase inhibitor pozopanib for VHL disease associated HB, with moderate success [ 75–78 ]. Other multityrosine kinase inhibitor trials for HB were disappointing, with the dovitinib trial discontinued owing to toxicity, while erlotinib and sunitinib were found to be of limited benefit [ 79–82 ]. Emerging research into HB neovascularization mechanisms – such as Twist1 signaling, described above – may provide additional anti-angiogenic therapeutic targets [ 26 ].…”
Section: Discussionmentioning
confidence: 99%